Integrating Traditional and Modern Methods to Optimize Arabic Language Learning for Generation Alpha - Achmad Bun Alim; Rafiandra Latif; Fajar Amin; Alif Cahya Setiyadi (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
Arabic language learning in Indonesia has been dominated by traditional methods that emphasize memorization, grammar mastery, and the study of classical texts. While these methods have the advantage of strengthening the scientific foundation, the Alpha generation, as a digital generation, requires a more interactive, visual, and technology-based approach. This study aims to analyze the relevance of traditional and modern methods and formulate an integrative strategy that can address the needs of the Alpha generation in Arabic language learning. The research method uses a library study by reviewing various academic literature related to Arabic language pedagogy, the characteristics of the Alpha generation, and digital learning innovations. The results show that the integration of the two methods can create a balance between the depth of language structure offered by traditional methods and the flexibility, interactivity, and creativity offered by modern methods. Thus, this integration has the potential to produce an adaptive, relevant, and sustainable learning model to improve the Arabic language competence of the Alpha generation.